Disproportionate collapse analysis of mid-rise cross-laminated timber buildings. Issue 11 (2nd November 2018) - Mpidi Bita, Hercend; Currie, Neil; Tannert, Thomas
Abstract: This paper investigates the structural behaviour of a twelve-storey Cross-Laminated Timber (CLT) building subjected to sudden removal of internal and external ground floor loadbearing walls, and computes the probability of disproportionate collapse. Analyses are carried out at three different structural idealisations, accounting for feasibility and complexity of finite elements models to understand their performance at: (i) the global, (ii) the component and (iii) the connection level. Focus is devoted on force and deformation-demands obtained from nonlinear dynamic analyses of the building. The demands are compared against the supply from common CLT panel sizes and the rotational stiffness ( k ) of the joints, detailed with off-the-shelf angle brackets and self-tapping screws. The study demonstrates that the applied forces and deformations required to develop resistance mechanisms are too large to be supplied by the proposed element and connection designs, if an internal ground floor wall is removed. The considered building has a probability of failure as high as 32% if designed without considerations of the complexities associated with disproportionate collapse. Consequently, to resist the effects of internal wall removal, the floors need to be redesigned and improved structural detailing with sufficient strength, stiffness and ductility is necessary to trigger collapse resistance mechanisms.